Boron and magnesium isotopic composition of seawater - Foster, G; Pogge von Strandmann, P; Rae, J (2010)
The isotopic systems of boron and magnesium are increasingly being used as proxies for a number of environmental variables and processes. The isotopic composition of seawater for both systems plays a central role in these studies and is an important interlaboratory standard. Given the long residence times of both elements (∼107 years) it is commonly assumed that seawater is isotopically homogenous for these systems, yet no systematic studies currently exist. Here we present the B and Mg isotopic composition of 26-28 seawater samples from a number of ocean basins that encompass a significant range in salinity (32 to 38 psu), temperature (-0.3 to +25.9C) and water depth (0 to 1240 m). We find no significant or systematic variation for either system in accordance with their long residence times. We recommend that the mean values we report (δ11B = 39.61 0.04 ‰ (2 s.e.; n = 28), δ25Mg = -0.43 0.01 ‰ (2 s.e.; n = 26), δ26Mg = -0.82 0.01 ‰ (2 s.e.; n = 26)) be used in future studies involving Mg and B isotopes. Copyright © 2010 by the American Geophysical Union.